The Russian Empire and the Soviet Union: too soon to talk of echoes? - Morrison, A (IB Tauris, 2014)
Russia is often considered to be an anomaly amongst the European empires, and its ambivalent status is further clouded by the seventy years of aggressively modernising Soviet rule that preceded its collapse. Across all its former territories, elements of the Soviet and even the Tsarist legacy are still live political issues: tangled borders, new nationalities, patterns of migration, strategic imperatives, and open warfare all function within the ghostly framework of the Russian Empire. This is so even though the destinies of its constituent parts over the last twenty years have been so divergent, ranging from EU membership for the Baltic States to a return to the personality cult in post-communist Turkmenistan. In part this is simply a function of the empire’s vastness, and accordingly any assessment, however brief and superficial (as this chapter inevitably will be), must take into a account the long process of Russian expansion, the different circumstances under which territories were incorporated into the empire, and their varied experiences of imperial or Soviet rule. As political circumstances within and outside the former USSR have changed, so, inevitably, have interpretations of Russian imperial history. Immediacy is what makes the Russian case truly distinctive: Russia’s relations with the former republics are far from postcolonial, and the Russian federation remains an imperial polity rather than a nation-state. Accordingly, we are not dealing with ‘echoes’ of imperialism here at all, but with a cacophony of urgent and immediate legacies.